The fading productivity of schooling in East Asia - Erich Gundlach; Ludger Wößmann (Journal of Asian economics, 2001)
We estimate changes in the productivity of schooling for six East Asian countries. Our productivity measure is based on changes in the relative price of schooling. A rising price of schooling relative to other labor-intensive service sectors should indicate declining relative schooling productivity. We find that the price of schooling increased by more than the price of other labor-intensive services in 1980-1994. We also find that the cognitive achievement of pupils did not change substantially, which suggests a constant quality of schooling output. Hence we conclude that schooling productivity has declined. The main reason for the fading productivity of schooling in East Asian countries appears to be a strong decline in the pupil-teacher ratio.
Keywords: I2; I2; 330; Asian Countries; Schooling; Productivity Growth; Bildungsinvestition; Schule; Bildungsniveau; Produktivität; Schätzung; Theorie; Ostasien; Hongkong; Japan; Philippinen; Singapur; Südkorea; Thailand